2020
DOI: 10.1155/2020/7162793
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Two Operation Methods Revealed the Risk Factors and the Necessity of LN-prRLN Dissection in Papillary Thyroid Carcinoma: A Retrospective Cohort Study in FUSCC

Abstract: Background. Although the American Thyroid Association (ATA) guidelines indicate that central lymph nodes posterior to the right recurrent laryngeal nerve (LN-prRLN) should be routinely dissected, pr-RLN dissection is often neglected due to the high risk of injury to the recurrent laryngeal nerve (RLN). The purpose of this study was to investigate the risk factors associated with LN-prRLN metastasis in patients with papillary thyroid carcinoma (PTC) by preoperative examination and the indications for LN-prRLN d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…Tumor size played an important role in LN-prRLN metastasis and was indicated as an independent risk factor of LN-prRLN metastasis in almost all reported models [12,22,23,[25][26][27]. In our study, we found that tumor size is positively correlated with LN-prRLN metastasis, and tumor size > 10mm was an independent predictor for LN-prRLN metastasis.…”
Section: Discussionsupporting
confidence: 59%
“…Tumor size played an important role in LN-prRLN metastasis and was indicated as an independent risk factor of LN-prRLN metastasis in almost all reported models [12,22,23,[25][26][27]. In our study, we found that tumor size is positively correlated with LN-prRLN metastasis, and tumor size > 10mm was an independent predictor for LN-prRLN metastasis.…”
Section: Discussionsupporting
confidence: 59%
“…The safety of LN-prRLN dissection is a point of concern. Wang et al (11) divided 1487 patients into two groups: the 378 patients who underwent CND with LN-prRLN dissection were defined as group A and the 1109 patients who underwent CND without LN-prRLN dissection as group B. Although group A had a higher incidence of hypocalcemia (7.4% vs. 4.0%, P=0.012), the two groups had similar rates of persistent hypocalcemia, transient and permanent recurrent laryngeal nerve palsies, chyle leakages, hematomas, and wound infections.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is increasing evidence that LN-prRLN metastases can occur in up to 26.6% of cN0 PTCs and that an additional removal procedure is not associated with an increased possibility of transient or permanent hypoparathyroidism or vocal cord paralysis (9)(10)(11)(12)(13)(14)(15). Common risk factors for LN-prRLN metastases include multiple foci, extrathyroidal extensions (ETE), right lobe tumors, tumor size, LN-arRLN metastases, and the number of positive LNs in the central neck.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to published studies, the incidence of LN-prRLN metastasis was 17. predictors such as age, male gender, tumor diameter, capsular invasion, comorbid adenoma, Hashimoto's thyroiditis, and VIa compartment lymph nodes metastasis were considered to be significantly associated with LN-prRLN metastasis (15)(16)(17)(18)(19)(20)(21)(22). Our center's data revealed that the incidence of LN-prRLN metastasis was 15.9%, but our multivariate analysis suggested that none of the indicators mentioned above were good predictors for the status of LN-prRLN.…”
Section: Discussionmentioning
confidence: 61%